Análise da fabricação de fio retangular de cobre eletrolítico, com seção de 3,5x8,8 mm a partir de vergalhão cilíndrico de diâmetro 8 mm - Roberto de Souza Oliveira (2009)
The application of the electrolytic copper rectangular wire, as a main component in the manufacturing of electric transformers windings, is directly associated to its dimensions and mechanical properties. These can be verified during the wire production process. The main objective of this work consists in evaluating the current production process of rectangular wire in a single pass, starting from the copper electrolytic rod 8 mm diameter on the production line of Toshiba Transmission andDistribuition of Brazil Ltda (Toshiba Transmissão e Distribuição do Brasil Ltda). Furthermore, this study intends to particularly analyze the final dimensions of the windings, presenting both the practical results and simulation of the process with the use of the Deform 3D software. The revision of the chosen bibliography, in this present study, presents not only the concepts and state of the art of the processes related to the rolling and drawing of copper wires, but also the Finite Element Method(FEM), whose base is used by the numeric simulation software. The methodology presents both a quantitative search of data and properties pertaining to the various stages of the production process and, qualitative results related to the numeric simulation of the rolling and drawing process. The process of rolling semi-processed material and the final product of the drawing are evaluated in relation to the mechanical and dimensional behavior. The results obtained in the experimental production and the equivalent simulations are presented and compared.